North Atlantic: The Most Dangerous Water in the World - Pivato, Joseph (Oltreoceano - Rivista sulle migrazioni, 2024)
During the twentieth century the North Atlantic became the most dangerous water on the planet. Hundreds of ships were sunk and thousands of men and women died in that cold grey water. We can begin with the Titanic disaster of 1912, The Empress of Ireland collision of 1914, the Lusitania torpedoed in 1915, and the Mont Blanc explosion of 1917. During World War II numerous ships and men were lost to the attacks of U-Boats. It is ironic then that this dangerous crossing is also the major route for the mass migration to North America and the search for a new life after World War II. One of these immigration ships, the Andrea Doria, collided with the MS Stockholm and sank in 1956. Long before the modern period of history, the North Atlantic brought disease and death to the Indigenous peoples of the New World. We will examine The Jesuit Relations as the record of all the interactions between the Indigenous peoples and the French colonists in the 1600s.The settlement of Quebec was founded in 1608 by the French explorer Samuel de Champlain who crossed the Atlantic approximately twenty times between France and North America. In the years 1634-1640 a major epidemic of smallpox and influenza killed thousands of Indigenous Wyandot people in New France and in the new English colonies to the south. Champlain died of an apparent stroke in 1635, but he could also have been infected with one of these diseases. In volume 13 of the Relations for year 1637 Père le Mercier records more than 130 references to fever, sickness, contagion, disease, epidemic, plague, dead children and bleeding. For the native populations of North America, the Atlantic Ocean brought destruction to their civilization and changed their history. What do the eyewitness accounts of the Jesuit missionaries tell us about human behaviour in crises of disease and death and possibly the search for martyrdom?